Chili and Ribiselkuchen: Thinking Community Gardening in Viennese municipal housing as shared Außenhaus - Mayrhofer, Rita (Momentum Quarterly, 2019)
Over the past ten years more than 70 community gardens have been established in the city of Vienna. So far, mainly people with above-average education and creative professions (creative class) have been able to fulfil their dream of community gardening. In contrast, people with a low level of education and socially disadvantaged groups are hardly represented in Viennese Community Gardens so far. To counteract this class bias and to activate unused spatial potentials at the same time were the aims of a pilot project that took place in the years 2009 to 2011 in a social housing area in Vienna. Based on data from action research and an empirical survey of the current situation, the text deals with the framework conditions, the participatory process and the effects of an autonomous community garden in the context of social housing. With the transformation of the functional distance green into a communal Außenhaus (Hülbusch 1978), new "spaces for action" in the sense of a vita activa were created (Arendt 1969). This case shows that community gardens can foster social inclusion in social housing areas. Particularly important are the principles of open space planning and a participation process aiming at self-determination.